แผลเก่า: จากฟรอยด์ ผ่านลากองสู่แนวคิดหลังอาณานิคม: Plae Kao : From Freud, Through Lacan, to Postcolonial Theory - วงศ์พุทธ, ทำนอง (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
This research aims to analyze the psychological content of the novel Plae Kao (The Scar) by synthesizing knowledge from Sigmund Freud’s psychoanalytic theory, Jacques Lacan’s concepts, and Postcolonial theory. The findings based on Freudian analysis suggest that the author, Mai Muang Doem, utilizes the rural world as an imaginary space to gratify the demands of the Id—instinctual desires that serve as an outlet from the aristocratic regulations and "civilized" constraints of the urban environment, which constitutes the author's original background. Lacanian analysis reveals that the metaphoric structure compresses Khwan’s personality traits of true love and recklessness together. Thus, the text subconsciously conveys that aggression is beauty, as it serves as an expression of authentic love. Meanwhile, metonymic communication establishes a connection that positions the rural setting in a state proximal to the Id, while Bangkok, representing civilized society, is situated closer to the Superego. From a Postcolonial perspective, the analysis finds that the author, as an urbanite, perceives the rural world through the character of Khwan, who functions as a hybrid figure. In certain respects, the author views the countryside through the text with a detached gaze, resulting in other rural characters being reduced to stereotypes of the "Other" characterized by weakness. Furthermore, the narrative techniques render Riam voiceless; consequently, she is portrayed entirely as a "woman lost to the city," making her eventual punishment appear justified within the logic of the text.